Metode SMART Dalam Pengambilan Keputusan Menentukan Monitor Terbaik Bagi Mahasiswa FTII Uhamka - Aji, Arielio Bayu; Rizkiawan, M. Asep; Sulaeman, Mia Kamayani; Wijaya, Farid Rizky (Jurnal Teknologi Dan Sistem Informasi Bisnis, 2024)
Technology continues to evolve to this day; computers are highly essential machines that aid humans in completing various tasks. Presently, computer usage has become a basic necessity for people across all walks of life, including professionals and students. Particularly for students, computer devices are crucial as they support learning activities, thereby enhancing both academic and non-academic pursuits. One vital component of a computer setup is the monitor, which displays visual outputs. There are numerous monitor technologies continually advancing, encompassing variations in screen sizes, resolutions, aspect ratios, and refresh rates. Brands are also developing various panel technologies such as LCD, LED, OLED, and MINILED. The wide array of monitor models available in the market often leaves students perplexed when selecting the best option. Hence, choosing the optimal monitor necessitates a decision support system (DSS). The technique employed in this decision-making process is the Simple Multi Attribute Rating Technique, commonly known as SMART. The outcomes derived from this method are notably precise, serving as reliable recommendations for selecting the best monitor for FTII Uhamka students.